Bolton's analysis using a photogrammetric method on occlusal photographs - Prasad Chıtra; Ashwin Prakash (Istanbul University, 2020)
Purpose The aim of the study is to present a photogrammetric technique using standardized occlusal photographs to perform Bolton's analysis and assess reliability of this new method with plaster study casts. Materials and Methods The study was conducted on 16 subjects (8 males, 8 females), aged 18-25 years. Standardized occlusal photographs and plaster study casts were obtained. The occlusal photographs were calibrated in Nemoceph® software. Mesio-distal dimensions of all teeth up to first molars were calculated and Bolton's analysis was performed. Similarly, a digital calliper with 0.1 mm sensitivity was used to measure mesio-distal dimensions of all teeth on plaster study casts to perform Bolton's analysis. 28 parameters were measured on study models and corresponding occlusal photographs. Paired t test and intraclass correlation tests were carried out to test validity and reliability of the photogrammetric method. An intraclass correlation test was calculated for 4 derived parameters to test reliability of Bolton's analysis measurements obtained from occlusal photographs as compared to study models. Results All 28 parameters showed a statistically significant and excellent correlation (r>.80) in the Intra Class Correlation test. 4 variables used to calculate Bolton's analysis showed statistically significant correlation (r>.96) in the intraclass correlation test. Conclusion Photogrammetry is a reliable tool to measure mesio-distal tooth size. Bolton's analysis from standardized occlusal photographs using the described photogrammetric technique can be used as an effective clinical tool.